Pharmacognostical standardization, antioxidant activity, and phytochemical analysis of leaves from enicostemma verticillatum - Sharma R.; Joshi A.; Pandey D.; Hemalatha S. (My University, 2025)
Pharmacognostical and physicochemical parameters were evaluated and quantified for Enicostemma verticillatum: foreign matter (2% w/w), loss on drying (4.3% w/w), total ash (9.6% w/w), acid insoluble ash (4.1% w/w), water-soluble ash (3.95% w/w), foaming index (< 100), and swelling index (4.1 mL.g-1); pesticide contents were within prescribed WHO limits. Phytochemicals present included phenol, tannins, flavanoids, steroids, alkaloids, saponins, carbohydrates, and rutin. In vitro antioxidant studies depicted potent antioxidant activity of ethanolic leaf extract that may be due to the presence of phenols, tannins, and flavonoids. © Taylor & Francis Group, LLC.